Tactile displays for auditory augmentation–A scoping review and reflections on music applications for hearing impaired users - Paisa, Razvan; Nilsson, Niels Christian; Serafin, Stefania (Frontiers in Computer Science, 2023)
The field of tactile augmentation has progressed greatly over the past 27 years and currently constitutes an emerging area of research, bridging topics ranging from neuroscience to robotics. One particular area of interest is studying the usage of tactile augmentation to provide inclusive musical experiences for deaf or hard-of-hearing individuals. This article details a scoping review that investigates and organizes tactile displays used for the augmentation of music from the field of hearing assistive devices, documented in 63 scientific publications. The focus is on the hardware, software, mapping, and evaluation of these displays, to identify established methods and techniques, as well as potential gaps in the literature. To achieve this purpose, a catalog of devices was created from the available literature indexed in the Scopus® database. We set up a list of 12 descriptors belonging to physical, auditory, perceptual, purpose and evaluation domains; each tactile display identified was categorized based on those. The frequency of use among these descriptors was analyzed and as well as the eventual relationship between them. Results indicate that the field is relatively new, with 80% of the literature indexed being published after 2009. Moreover, most of the research is conducted in laboratories, with limited industry reach. Most of the studies have low reliability due to small sample sizes, and sometimes low validity due to limited access to the targeted population (e.g., evaluating systems designed for cochlear implant users, on normal hearing individuals). When it comes to the tactile displays, the results show that the hand area is targeted by the majority of the systems, probably due to the higher sensitivity afforded by it, and that there are only a couple of popular mapping systems used by the majority of researchers. Additional aspects of the displays were investigated, including the historical distribution of various characteristics (e.g., number of actuators, or actuators type) as well as the sonic material used as input. Finally, a discussion of the current state of the tactile augmentation of music is presented, as well as suggestions for potential future research.